2019
DOI: 10.1101/534396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics of Beta Waveform Shape in Parkinson’s Disease Detected with Scalp Electroencephalography

Abstract: Neural activity in the beta frequency range (13-30 Hz) is excessively synchronized in Parkinson's Disease (PD). Previous work using invasive intracranial recordings and non-invasive scalp electroencephalography (EEG) has shown that correlations between beta phase and broadband gamma amplitude (i.e., phase-amplitude coupling) are elevated in PD, perhaps a reflection of this synchrony. Recently, it has also been shown, in invasive human recordings, that nonsinusoidal features of beta oscillation shape also chara… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…In our results we observed a decrease in the coupling of cardiac sympathetic activity with brain connectivity measured in the alpha and gamma bands. EEG studies have revealed significant changes in the alpha-gamma range in PD, with reduced connectivity in alpha-beta bands and increased connectivity in the gamma band (12), but also aberrant cortical synchronization in the beta band (17,18). It remains to be confirmed whether our results relate to the repeatedly reported changes in brain connectivity in PD, including subcortical structures.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In our results we observed a decrease in the coupling of cardiac sympathetic activity with brain connectivity measured in the alpha and gamma bands. EEG studies have revealed significant changes in the alpha-gamma range in PD, with reduced connectivity in alpha-beta bands and increased connectivity in the gamma band (12), but also aberrant cortical synchronization in the beta band (17,18). It remains to be confirmed whether our results relate to the repeatedly reported changes in brain connectivity in PD, including subcortical structures.…”
Section: Discussionsupporting
confidence: 53%
“…In recent years, PD has been recognized as a condition that affects physiology at a network level, rather than just a focal brain region pathology (15,16). One of the physiological signatures of PD are the aberrant changes in brain connectivity, whose origin remains to be understood (17,18). We propose a new framework to study brain-heart interactions by quantifying the relationship between brain connectivity and estimators of cardiac sympathetic and parasympathetic activities.…”
Section: Introductionmentioning
confidence: 99%